Sexual Dimorphism in Superadded Teeth - A Cross Sectional Study Conducted among Students of South Indian States - Pavan Kumar G; Dileep Kumar R; Hemanth Raj M N; Anand Patil (Indian Journal of Forensic Medicine & Toxicology, 2021)
The present cross sectional study was conducted on students of south Indian states of SSIMSRC, Davangere.A study casts of 200 was taken (104 males and 96 females) in the age group of {18-25} years. The Mesiodistal and Buccolingual diameters of first and second permanent molars of both maxillary and mandiblewere measured on the study casts, using sliding verneir callipers.The buccolingual and mesiodistal dimensions measured, in both maxillary and mandibular molars, showedhigher values in males compared to that of females. Amongst the parameters studied, the buccolingualdimensions of maxillary molars showed highest sexual dimorphism with an accuracy of 82.1% and themesiodistal dimension exhibited least sexual dimorphism. In present study showed that the maxillary molarsexhibited highest percentage of dimorphism, compared to the dimensions of mandibular molars, the existenceof statistically significant sexual dimorphism in maxillary molars especially the first maxillary molars.